The influence of prices, facilities, and promotions on customer satisfaction at Grand Darmo Suite Surabaya - Harun Alrasyid Oktabar Sutomo; Ec. R. Agus Baktiono (NAROTAMA UNIVERSITY, Indonesia, 2019)
Grand Darmo Suite Surabaya Hotel has many determinants in customer satisfaction, these factors are Price, Facilities, and Promotion. And these factors will be examined statistically which aims to determine how much influence the price, facilities, and promotions on customer satisfaction Grand Darmo Suite Surabaya Hotel. The population in this study were guests of the Grand Darmo Suite Hotel Surabaya, who were staying at this hotel. While the determination of samples on customer satisfaction will use a purposive sampling technique, and the data used is primary data with a sample of 85 respondents. The analysis technique used is multiple linear regression analysis. Based on the results of the study indicate that the variables of price, facilities, and promotions have a significant effect on customer satisfaction. And in terms of the closeness between prices, facilities, and promotions on customer satisfaction, the Grand Darmo Suite Surabaya Hotel has a fairly high relationship.